2016
DOI: 10.1002/dneu.22412
|View full text |Cite
|
Sign up to set email alerts
|

The immunoglobulin‐like superfamily member IGSF3 is a developmentally regulated protein that controls neuronal morphogenesis

Abstract: The establishment of a functional brain depends on the fine regulation and coordination of many processes, including neurogenesis, differentiation, dendritogenesis, axonogenesis, and synaptogenesis. Proteins of the immunoglobulin-like superfamily (IGSF) are major regulators during this sequence of events. Different members of this class of proteins play nonoverlapping functions at specific developmental time-points, as shown in particular by studies of the cerebellum. We have identified a member of the little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 77 publications
4
28
0
Order By: Relevance
“…Lesion-induced reformation of synapses caused IgSF8 to reappear in terminals, whereas blocking olfactory activity prevented the disappearance of IgSF8 from mature synapses 106 . Similarly, the EWI-subfamily member IgSF3 transiently localizes to developing cerebellar GC axon terminals 107 . The localization of IgSF8 to the MF bouton and filopodia suggested a functional requirement for IgSF8 at both sites.…”
Section: Discussionmentioning
confidence: 99%
“…Lesion-induced reformation of synapses caused IgSF8 to reappear in terminals, whereas blocking olfactory activity prevented the disappearance of IgSF8 from mature synapses 106 . Similarly, the EWI-subfamily member IgSF3 transiently localizes to developing cerebellar GC axon terminals 107 . The localization of IgSF8 to the MF bouton and filopodia suggested a functional requirement for IgSF8 at both sites.…”
Section: Discussionmentioning
confidence: 99%
“…Other published functions are HIV-1 entry regulation (e.g., CD63 regulates CXCR4 HIV co-receptor expression on cell surface), reverse transcription (e.g., CD81 regulates SAMHD1 turnover), assembly and trans-infection (Suárez et al, 2018). TSPAN7, in addition to its recently discovered role in control of HIV transfer through regulation of actin nucleation (Ménager and Littman, 2016), has been found to be mutated in some forms of X-linked intellectual disabilities, which may be explained by the role of this protein in neuronal morphogenesis (Bassani et al, 2012;Usardi et al, 2017). Indeed, TSPAN7 regulates dendritic spines and filopodia formation in neurons and promotes axonal branching (Bassani et al, 2012;Usardi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…TSPAN7, in addition to its recently discovered role in control of HIV transfer through regulation of actin nucleation (Ménager and Littman, 2016), has been found to be mutated in some forms of X-linked intellectual disabilities, which may be explained by the role of this protein in neuronal morphogenesis (Bassani et al, 2012;Usardi et al, 2017). Indeed, TSPAN7 regulates dendritic spines and filopodia formation in neurons and promotes axonal branching (Bassani et al, 2012;Usardi et al, 2017). This protein is also believed to play a role in cancer as it promotes migration and proliferation of lung cancer cells and limits myeloma tumor development (Cheong et al, 2015;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…TSPAN7 is a member of the transmembrane 4 superfamily, also called the tetraspanin family, which includes proteins characterized by four transmembrane domains, with one short and one large extracellular loop (20). Previous studies have found that in cerebellar granule cells, TSPAN7 promotes axonal branching, and the size of TSPAN7 clusters is increased by downregulation of IGSF3 expression, which might be at the center of a new signaling pathway controlling brain development (21). In oral tongue squamous cell carcinoma, differential methylation of TSPAN7 was found to be predictive of certain clinical and epidemiologic parameters (22).…”
Section: Discussionmentioning
confidence: 99%